Inside the radicalized mind: the neuropolitics of terrorism and violent extremism - Howard, Tiffiany (Cambridge elements : elements in experimental political science, 2025)
This Element aims to better understand the role of the internet in the radicalization process, focusing on how online factors contribute to self-radicalization. Specifically, it examines the neurocognitive process of online radicalization by analyzing the impact of terrorist and extremist propaganda videos on individuals' cognitive empathy using electroencephalography (EEG). Ultimately, this research aims to provide a more comprehensive understanding of online radicalization and the psychological effects of exposure to extremist content on the internet.